A marine biofilm flow cell for in situ determination of drag and biofilm structure. (15th April 2019) - Fabbri, Stefania; Dennington, Simon; Price, Clayton; Longyear, Jennifer; Stoodley, Paul
Abstract: It is not straightforward to link biofilm parameters to frictional drag, because of the heterogeneous distribution and viscoelasticity of the produced matrix. Here we present the design and calibration of a flow cell in which marine biofilms can be cultured under flow and then assessed for drag, structural and mechanical properties. The flow cell test section comprised a rectangular channel constructed by sandwiching together rigid PVC panels and side panels of clear acrylic, which allow natural light to enter. The Fanning friction factor (Cf ) of the flow cell was found by measuring the pressure drop (ΔP) at various flow velocities ( u ). Flow cell calibration was carried out using a clean inert marine coating, and various roughness grades of sandpaper sheets to find Cf for each rigid roughness. ΔP was proportional to u 2, indicating flow was turbulent (R 2  = 0.99). The top panel of the flow cell can be substituted with a clear acrylic lid to allow simultaneous measurement of Cf and biofilm physico-mechanical properties by optical coherence tomography (OCT). Here, we demonstrated that the flow cell can be used to image microbial fouling using OCT. Future experiments will assess physico-mechanical and drag properties of marine fouling biofilms under flow.